Primary pigmented nodular adrenocortical disease associated with Carney complex: case report and literature review - Gonçalves, Fabrícia Torres; Feibelmann, Taciana Carla Maia; Mendes, Cínthia Monteiro; Fernandes, Maria Luiza Mendonça Pereira; Miranda, Geraldo Henrique Gouvêa de; Gouvêa, Agostinho Pinto; Jorge, Paulo Tannús (São Paulo Medical Journal, 2006)
CONTEXT: Carney complex (CNC), a familial multiple neoplasm syndrome with dominant au- tosomal transmission, is characterized by tumors of the heart, skin, endocrine and peripheral nervous system, and also cutaneous lentiginosis. This is a rare syndrome and its main endocrine manifestation, primary pigmented nodular ad- renal disease (PPNAD), is an uncommon cause of adrenocorticotropic hormone-independent Cushing’s syndrome. CASE REPORT: We report the case of a 20 year old patient with a history of weight gain, hirsutism, acne, secondary amenorrhea and facial lentiginosis. Following the diagnosing of CNC and PPNAD, the patient underwent laparoscopic bilateral adrenalectomy, and she evolved with decreasing hypercortisolism. Screening was also performed for other tumors related to this syndrome. The diagnostic criteria, screening and follow-up for patients and af- fected family members are discussed.